Cancer‐related genetic variants of Helicobacter pylori strains determined using gastric wash‐based whole‐genome analysis with single‐molecule real‐time technology. Issue 1 (11th September 2020) - Watanabe, Yoshiyuki; Oikawa, Ritsuko; Kodaka, Yasuhiro; Sato, Yoshinori; Ono, Shoko; Kenmochi, Takeshi; Suzuki, Hideo; Futagami, Seiji; Kato, Mototsugu; Yamamoto, Hiroyuki; Itoh, Fumio
Abstract: Helicobacter pylori ( H . pylori ) are a primary factor in the pathogenesis of gastric cancer (GC); GC ranks third among cancer‐related mortality. A clear understanding of the H . pylori genome factors underlying GC is necessary to develop more effective methods to prevent GC. A single‐molecule real‐time DNA sequencing‐based H . pylori genome‐wide association study analysis was performed using the H . pylori genome present in five early‐stage GC (EGC) and five non‐GC clinical DNA samples recovered from gastric washes. A total of 275 genes with 702 nucleotide variants (NVs) were found to be common to three or more patients with EGC but no non‐GC patients (single‐NV: 654/702, 93.2%; multi‐NV: 40/702, 5.7%; deletion: 3/702, 0.4%; insertion: 3/702, 0.7%). Gene ontology analysis of H . pylori revealed that genes involved in the mitochondrial electron transport system, glycolytic processes and the TCA cycle were highly enriched. Cancer‐related NVs were most frequently found in a member of the Helicobacter outer membrane protein family, hopL . In particular, one of the NVs in hopL was a novel six‐nucleotide insertion (1159095̂1159096, TACTTC); this mutant was detected more frequently in a validation set of 50 additional EGC samples (22/50, 44.0%) than in 18 non‐GC samples (3/18, 16.7%, P = .04). These results suggest that the hopL variant is associated with the development of GC and may serve as a genetic biomarker of H . pylori virulence and GC risk. Our assay can serve as a potent tool to expand our understanding of bacteria‐associated tumorigenesis. Abstract : What's new? Helicobacter pylori is a primary factor in the pathogenesis of gastric cancer. A clear understanding of the H. pylori genome factors underlying gastric cancer remains elusive. Based on next‐generation sequencing of gastric wash samples, here the authors analyzed virulence factors in the H. pylori genome obtained from the entire stomach. They identified 275 genes with 702 nucleotide variants that were common to gastric cancer patients. A novel variant in the Helicobacter outer membrane protein family was detected frequently in a validation set of samples. These results may help introduce preventive measures for patients infected with high‐risk H. pylori strains.